A review of ventilation and cooling systems for large-scale pig farms. (February 2023) - Hu, Zhiru; Yang, Qizhi; Tao, Yao; Shi, Long; Tu, Jiyuan; Wang, Yong
Highlights: Cooling challenges arising from large-scale modern farm summarized. Methods to ensure indoor environmental parameters introduced. Recommendations for sustainable production of large-scale pig farms made. Future research directions of cooling systems proposed. Abstract: Due to the rapid development of modern livestock husbandry, the effectiveness and energy efficiency of cooling systems used in farming buildings have come to the public's attention. Traditional cooling systems may not satisfy the sizable cold load and the environmental requirements of the large-scale pig farms, characterized as high density and large groups. This article reviews applications of cooling systems for large-scale pig farms from three aspects: the cold source that affects the energy efficiency and sustainability of the system, the cooling terminal that satisfies the thermal demand of pigs, and the ventilation method that determines indoor air quality and biosecurity. The feasibility of artificial cold sources applied to large-scale pig farms is pointed out. The cooling principles and effects of common cooling terminals are compared. Furthermore, comparing different ventilation methods shows that individual ventilation and combined ventilation of supply and exhaust fans may be the development direction of ventilation systems for large-scale pig farms. The conclusions drawn in this review provide a systematic reference for the application of cooling systems to facilitate the achievement of the goal of efficient and sustainable production in large-scale pig farms.